2009
DOI: 10.5194/acp-9-5299-2009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of balloon and satellite water vapour measurements in the Southern tropical and subtropical UTLS during the HIBISCUS campaign

Abstract: Abstract. Balloon water vapour in situ and remote measurements in the tropical upper troposphere and lower stratosphere (UTLS) obtained during the HIBISCUS campaign around 20 • S in Brazil in February-March 2004 using a tunable diode laser (µSDLA), a surface acoustic wave (SAW) and a Vis-NIR solar occultation spectrometer (SAOZ) on a long duration balloon, have been used for evaluating the performances of satellite borne remote water vapour instruments available at the same latitude and measurement period. In … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 76 publications
1
13
0
Order By: Relevance
“…As an example, Fig. 10 shows the in situ measurements performed during a balloon slow descent between 20 and 12 km on 13 February together with the closest available satellite observations (Montoux et al, 2009). The µSDLA and SAW measurements in the upper troposphere show super-saturated mixing ratios (MR) up to the Lapse Rate Tropopause (LRT) at 15.2 km above which, the MR ranges between 3.5 and 5 ppm.…”
Section: Hydration Of the Lower Stratosphere Over Land Convective Sysmentioning
confidence: 99%
See 2 more Smart Citations
“…As an example, Fig. 10 shows the in situ measurements performed during a balloon slow descent between 20 and 12 km on 13 February together with the closest available satellite observations (Montoux et al, 2009). The µSDLA and SAW measurements in the upper troposphere show super-saturated mixing ratios (MR) up to the Lapse Rate Tropopause (LRT) at 15.2 km above which, the MR ranges between 3.5 and 5 ppm.…”
Section: Hydration Of the Lower Stratosphere Over Land Convective Sysmentioning
confidence: 99%
“…Using the same statistical method employed for ozone, Montoux et al (2009) (Fig. 20) showed that in the stratosphere, above 20 km, HALOE displays the best precision (2.5%), followed by SAGE II (7%), MI-PAS (10%), SAOZ (20-25%), GOMOS (25%) and SCIA-MACHY (35%).…”
Section: Water Vapourmentioning
confidence: 99%
See 1 more Smart Citation
“…JLH and HWV agreed well during several field campaigns prior to 2003, after which JLH began to agree well with CFH and MLS. 3,13 To address these long-standing discrepancies, the CFH, JLH, FISH, and HWV instruments were compared under controlled laboratory conditions during the Aqua Validation and Intercomparison Experiment (AquaVIT) at the aerosol and cloud simulation chamber in Karlsruhe, Germany. 14 The comparison showed that all instruments agreed to within 0.4 ppmv in the lab, a stark contrast from the 1.5-2 ppmv disagreements in flight.…”
Section: Introductionmentioning
confidence: 91%
“…15 Such satelliteborne remote instruments as Microwave Limb Sounder (MLS)/Aura, Atmospheric Infrared Sounder (AIRS)/Aqua, COSMIC/FORMOSAT-3 or SAPHIR/Megha-Tropiques, retrieve profiles of water vapor in the troposphere and in the stratosphere. 15 Such satelliteborne remote instruments as Microwave Limb Sounder (MLS)/Aura, Atmospheric Infrared Sounder (AIRS)/Aqua, COSMIC/FORMOSAT-3 or SAPHIR/Megha-Tropiques, retrieve profiles of water vapor in the troposphere and in the stratosphere.…”
Section: Validation Of Satellites Water Vapor Measurementsmentioning
confidence: 99%